EFFECT OF PRIOR KNOWLEDGE OF BEHAVIOURAL OBJECTIVES ON MATHEMATICS ACHIEVEMENT OF HIGH AND LOW MENTAL ABILITY SECONDARY SCHOOL STUDENTS IN IMO STATE, NIGERIA - Osuafor, Abigail; Njoku, Celestine (PEOPLE: International Journal of Social Sciences, 2016)
The high rate of failure in external mathematics examination among secondary school students in Nigeria calls for great concern. The sole use of conventional methods by mathematics teachers in teaching could be one of the factors that lead to high rate of failure in mathematics examinations. Against this background, this study determined the effect of prior knowledge of behavioural objectives on Mathematics achievement of high and low mental ability secondary school students in Imo State, Nigeria. Two research questions and two null hypotheses provided focus to this study. Quasi experimental design specifically the pre-test, post-test non-equivalent control group design was adopted. A sample of 94(45 male and 49 female) mathematics students with average age of 15 years was used for the study. Two instruments: General Mental Ability Test (GMAT) and Mathematics Achievement Test (MAT) were used for data collection. The instruments were face and content validated by experts. The reliability of MAT was established using Kuder Richardson formula 21 (KR-21) for section A and Cronbach alpha for section B and were found to have internal consistency of 0.99 and 0.86 respectively. The reliability of GMAT was ascertained using Kuder Richardson formula 21 (KR-21) which yielded an internal consistency of 0.99. Mean was used to answer the research questions while Analysis of Co-variance (ANCOVA) was used to test the hypotheses at 0.05 level of significant. Results showed that: High mental ability students who had prior knowledge of behavioural objectives performed better than the high mental ability students who did of behavioural objectives performed better than the low mental ability students who did not have prior knowledge of behavioural objectives. Based on the findings, the researcher recommended that mathematics teachers should expose learners to the knowledge of behavioural objectives before the lesson’s content development begins.